Increasing energy and resource efficiency through innovation: an explorative analysis using innovation survey data - Klaus Rennings; Christian Rammer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
Energy and resource efficiency innovations (EREIs) are often seen as win-win opportunities for both the economic and the environmental performance of firms. It is thus worth asking how the innovation activities and performance of firms with regard to energy and resource efficiency look like: Do EREI firms follow distinct innovation strategies? Do EREIs spur or limit innovation success? And what are the particular features of EREI firms compared to conventional innovators? Using German innovation data, we find that EREIs are determined by a larger set of technology-push and market-pull factors. On the supply side, R&D budgets, research infrastructure and networking with other firms are important factors of influence, while on the demand side increased productivity and cost reductions are decisive, as well as improved product quality. On the other hand, EREIs are complex activities which also need regulatory incentives. Although EREIs are not more successful compared to conventional innovations, they contribute substantially to the economic success of firms.
Keywords: Q01; Q55; O31; O33; 330; Resource efficiency; energy efficiency; environmental innovations; innovation surveys; Innovation; Energiesparen; Umwelttechnik; Öko-Effizienz; Unternehmensentwicklung; Kosten; Deutschland